Dyslipidemia (IntechOpen, 2021)
Dyslipidemia is a major risk factor for cardiovascular disease, which is the leading cause of morbidity and mortality around the globe, particularly among aging populations. Lipoprotein disorders, frequently encountered by clinicians, require early recognition and treatment. In this book, we assembled a group of world-renowned scholars in their field to address major areas in lipoprotein disorders that are imminently relevant to clinicians and other healthcare providers. Areas discussed include an overview of lipid metabolism, a complex topic, presented in a simplified and rational way. We also highlight recent developments in the field including dyslipidemias characterized by nontraditional lipid biomarkers. Furthermore, we discuss the pathogenesis of atherosclerosis and the role of dyslipidemia. Other chapters include the assessment of primary and secondary causes of dyslipidemia. Targets for treatment as well as the role of major therapeutic agents including statins and PCSK9 inhibitors are also discussed in light of the most recent guidelines by major international organizations. This is in addition to an overview of lifestyle and dietary modification as well as alternative options for dyslipidemia management. Furthermore, dyslipidemia in special populations is emphasized including various ethnic groups as well as those with HIV disease, chronic kidney disease, among others. The role of adiposity including brown fat together with highlights on lipidomics and dyslipidemias characterized by nontraditional lipid biomarkers is also highlighted. We believe that this volume will serve as a valuable resource, not only for clinicians and other healthcare providers, but for students and research scholars as well.